Conflict Analysis between Online Ojek and Conventional Ojek in Makassar City - Zohrah N; Eko Prasetyo (Program of Communication Sciences, Faculty of Social and Political Sciences, UIM, 2018)
This study presents three formulations of the problem, namely, what is the opinion of a conventional ojek for the presence of online ojek transportation, how is the opinion of an online ojek in responding to the existence of a conventional ojek and how conflicts and solutions that occur with the presence of an online ojek to conventional base taxi drivers. Based on the formulation of the problem, this study aims to finding out the opinion of conventional ojek for the presence of online ojek transportation facilities, finding out the opinion of online ojek drivers in responding to the existence of a conventional ojek and finding out the conflicts and solutions that occur with the presence of an online ojek to conventional base taxi drivers. This research employs qualitative descriptive method, using juridical and sociological approaches, and selecting several informants with snowball sampling and purposive sampling. The source of the data used is the primary source, namely information that comes from direct observation to the research location employing observation and interviews. Whereas secondary sources are, data obtained from literature studies to complete primary data. Data collection is done through field research, observation, and interviews. The results show that what is more needed to resolve conflicts between online ojek and conventional ojek is a clear rule. The conflict between online ojek and conventional ojek in Makassar City is temporarily overcome by the existence of an operational ban zone for online ojek transportation.